2019
DOI: 10.1186/s12879-019-4025-0
|View full text |Cite
|
Sign up to set email alerts
|

First case report of inducible heart block in Lyme disease and an update of Lyme carditis

Abstract: Background Lyme disease (LD), is the most common vector-borne illness in the US and Europe, with predominantly cutaneous, articular, cardiac and neuro-psychiatric manifestations. LD affects all layers of the heart and every part of the conducting system. Carditis is a less common manifestation of LD. Heart block (HB) as the initial and sole manifestation of LD is rare. Inducible HB has never been reported in LD. We report a case of heart block (HB) inducible with exercise and reversible with rest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Nevertheless, isolated conduction system disturbances are not uncommon in infectious diseases; for example, Lyme disease can present with similar manifestations. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, isolated conduction system disturbances are not uncommon in infectious diseases; for example, Lyme disease can present with similar manifestations. 5 …”
Section: Discussionmentioning
confidence: 99%
“…The vector that carries the infective agent can be found in places where it has never been found before (Estrada-Peña et al, 2018), and these tick distribution and density changes have been shown to be related to changes in climate (Liang and Gong, 2017). If it is not immediately recognized and treated, it can be a life-threatening disease with multiple cardiac and neurological manifestations (Kannangara et al, 2019). Lyme carditis (LC) is a rare manifestation of LD that includes: heart conduction abnormalities, myocarditis, pericarditis, endocarditis, pancarditis, arrhythmias, dilatative cardiomyopathy and congestive heart failure, myocardial infarction, and coronary aneurysms (Hidri et al, 2012;Kostić et al, 2017).…”
Section: Lyme Endocarditis Highlightsmentioning
confidence: 99%
“…Lyme endocarditis (LE), one possible manifestation of LC, is rare and has been the subject of case reports. Due to climate change, an increased incidence rate of LC with involvement of heart valve can be expected (Lindgren and Jaenson, 2006;Liang and Gong, 2017;Estrada-Peña et al, 2018;Kannangara et al, 2019).…”
Section: Lyme Endocarditis Highlightsmentioning
confidence: 99%
“…An estimated 300,000 people are diagnosed with LD each year in the United States [ 1 , 6 ] with most cases frequently occurring in New England and the Atlantic states [ 4 , 6 ]. The highest prevalence is during the Spring and Summer months, when the deer and ticks are most active.…”
Section: Discussionmentioning
confidence: 99%